السياسة المالية الفرنسية في الجزائر 1830-1962م - بودلاعة, رياض (جامعة الوادي - University of Eloued, 2021)
مثلت السياسة المالية الفرنسية التي طبقت في الجزائر إبان فترة الاحتلال عنصرا بالغ الأهمية من عناصر السياسة الاستعمارية التي كانت تهدف إلى ترسيخ الوجود الفرنسي في الجزائر و إخضاعها للفئة الكولونيالية و فتحها أما الاستغلال الرأسمالي . ويهدف هذا المقال إلى إبراز مختلف المراحل التي مرت بها السياسة المالية في الجزائر، والعوامل المختلفة التي تحكمت في تباين هذه السياسة طيلة فترة الاحتلال و التعريف بمختلف المؤسسات والمجالس المالية التي أقيمت في الجزائر لإدارة مالية البلاد، و إبراز الطابع العنصري لهذا النظام المالي الذي جاء لخدمة الفئة الكولونيالية على حساب المجتمع الجزائري . The French financial policy that was applied in Algeria during the occupation period represented a very important element of the colonial policy, which was aimed at consolidating the French presence in Algeria, and subjecting it to the colonial category and opening it up as for capitalist exploitation.This article aims to highlight the various stages that the financial policy went through in Algeria, and the various factors that governed the variation of this policy throughout the occupation period, idenfying the various financial institutions and councils that were established in Algeria to manage the country's finances, and highlighting the racist nature of this financial system that came To serve the colonial category at the expense of the Algerian society.
مقال
Keywords: السياسة المالية، الاستقلال المالي للجزائر، المجالس المالية، بنك الجزائر، الضرائب العربية; Financial policy , financial independence of Algeria, ,financial councils ,Bank of Algeria, Arab taxes